Pinus halepensis Mill. architectural analysis for fuel modelling - Caraglio Y.; Pimont F.; Rigolot E. (Proceedings of the international workshop MEDPINE 3: conservation, regeneration and restoration of Mediterranean pines and their ecosystems, 2007)
A fire behaviour model based on the complete physical and multiphase approach has been developed in order to study fuel treatment efficiency at the wild land urban interface. Pinus halepensis stands are fire prone communities very common in South Eastern France. The architectural approach was applied to describe Pinus halepensis fine fuel distribution in order to build up inputs for the fire model. The plant architectural software AMAPsim developed by Cirad which relies on both qualitative and quantitative tree architecture description and leads to realistic 3D computing trees can be used to complement fuel characterization. From the computerized plant architecture model it is possible to access and extract various physical parameters. These spatialized data then could be used in fire propagation model. This paper focuses on Pinus halepensis fine fuel characterization using AMAP tools. The AMAP methodology is presented as well as the data collected for plant growth and architecture modelling. Results on the main features of Pinus halepensis architecture are presented as well as Aleppo pine simulations of individual plants in order to extract fuel parameters. The first results of fire simulations in Aleppo pine stands are presented and the capabilities and limits of such an approach for fuel modelling are discussed.
Proceedings of the International Workshop, 2005/09/26-30, Bari (Italy)